PENGARUH TOTAL ASSET TURN OVER, RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP ACCUMULATION DISTRIBUTION LINE - Luna Haningsih; Zulkifli Zulkifli; Caturida Meiwanto Doktoralina (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
Fundamental and technical analysis is used by analysis to predict the trend ofstock price and trading volume. Studies conducted aimed to determine the effect of fundamental analysis to technical analysis. Combining two forms of analysis can produce a more accurate prediction of the stock price movement of listed cement companies in Indonesia Stock Exchange. Research experts indicate that the fundamental and technical analysis can be used independently with the ability to predict stock price movements. This study combines both analysis in a model that can provide a more robust predictive capability in the Company's share price movements of cement. Fundamental analysis is the economy wide scope, one of the predictions of financialÂ performance. In this study the total asset turnover, return on assets and return on equityto determine which stocks are pretty good. While technical analysis is usedaccumulation distribution line that has a better ability to predict future stock prices because the data contained technical stock price and trading volume to determine when to buy and sell momentum. These results indicate that the total asset turnover, return on assets and return on equity significantly influence the accumulation distribution line. While the individual that the return on equity has no significant effect. The results of this study are expected to improve knowledge for the readers, especially investors in order to obtain optimal benefits.